OPTIMIZATION OF SLOPE GEOMETRY IN THE HIGHWALL SECTION A-A’ OF THE MAHAYUNG PIT, MUARA ENIM, SOUTH SUMATRA - Zhafira, Zhafira; Zakaria, Zufialdi (Universitas Padjadjaran, 2026)
Slope stability is a critical factor in open-pit mining operations that directly affects safety and production continuity. This study aims to evaluate the design safety factor of the Mahayung Pit for 2026 and to optimize the slope geometry of Highwall Section A–A' using the Morgenstern-Price limit equilibrium method with Mohr-Coulomb failure criteria under actual and fully saturated groundwater conditions. The evaluation results indicate that the slope does not yet meet the minimum safety factor threshold; therefore, optimization was performed by adjusting the slope geometry. This optimization yielded a minimum safety factor (SF) of 1.496 under saturated conditions, meeting the standard requiring SF ≥ 1.3. Consequently, this can serve as a basis for revising the Mahayung Pit design to support safer and more efficient mining operations.